The Concept of Trust in Leadership: A Comparison of the Tafsir of Al-Munir and Al-Azhar in Interpreting Surah An-Nisa':58 - Hanifah, Widad Fatin; Mufid , Miftarah Ainul; Mashuri , M. Mukhid; Zainuddin, Ahmad (Literacy: Journal of Education and Social Science, 2024)
The general meaning of the word amanah in Surah an-nisa' verse 58 is the mandate to enforce the law of Allah fairly, both in personal life, society or state. In addition, another meaning of trust in this verse is that the position or mandate must be handed over to the person who has the right to carry it, anytime and anywhere. In the context of the life of the nation and state, all positions must be handed over to those who have gone through the legal or democratic process in obtaining the mandate. In this study, a literature method is used that involves collecting data analysis from various relevant sources such as books, tafsir books, and articles related to tafsir al-Munir and al-Azhar surah an-nisa' verse 58. This study aims to compare and analyze the interpretation of Surah an-nisa' verse 58 from the perspective of Tafsir al-Munir and al-Azhar. The results of this study found differences and similarities between Tafsir al-Munir and al-Azhar. Wahbah Zuhaili interprets the word amanah in this verse to include a broad meaning, meaning all types of trusts that exist, both trusts related to oneself or related to the rights of others as well as trusts related to Allah. Meanwhile, Buya Hamka interpreted that the mandate should be given to someone who is indeed an expert. The same interpretation of the two says that maintaining trust is one of the main keys in Islamic religious teachings.